The Correlation amongst Self-Directed Learning, Personality Traits and Writing Ability - Aristya Dwi Juliani; Sabarun; Siminto (Universitas Sarjanawiyata Tamansiswa, 2024)
Abstract: Proficiency in writing is an essential requirement for English learners as a second language. There is a correlation between the ability to effectively organize and structure written words and the diversity of self-directed learning and personality traits exhibited by students. This study investigated the potential association between Self-Directed Learning, Personality Traits, and Writing Ability. The study included students enrolled in the English Education department at IAIN Palangka Raya who were taking a course on paragraph writing. This study employed a correlation design. The reseacher adapted the 25 item Self-Rating Scale of Self-Directed Learning (SRSSDL) designed by Willimson (2007), International Personality Item Pool (IPIP-BFM-25) designed by Akhtar and Azwar (2019) and students paragraph writing test. Self-Directed Learning (X1) and the Personality Traits (X2) simultaneously had a effect on the Writing Ability (Y). The Coefficient of Determination (R) is 85.0%, indicating that the amount of contribution of X1 and X2 simultaneously. Then the R2 = 0.72% meaning that both variable gave contribution about 72.00%. Effective Contribution (SE) each variable Self-Directed Learning (X1) and Personality Traits (X2) individually is 09.96% and 61.60% to the Writing Ability (Y). The total contribution is 71.56%.